Association of Intensive Endoscopic Burden with Esophageal Cancer Detection: A Nationwide Cohort Study - Yeunji Lee; Eunyoung Lee; Bumhee Park; Gil Ho Lee; Sun Gyo Lim; Sung Jae Shin; Choong-Kyun Noh; Kee Myung Lee (Gut and Liver)
Background/Aims: Early diagnosis of esophageal cancer (EC) remains challenging despite the increasing frequency of endoscopic screenings globally. The rapidly increasing number of endoscopic screenings performed over a certain period might influence diagnostic performance. This study evaluated the association between the number of endoscopic screenings and EC detection rates in a nationwide cohort. Methods: This retrospective population-based study used the Korean National Cancer Screening Program database, comprising 32,774,742 males and females aged ≥40 years between 2015 and 2019. Negative binomial regression model and least-squares mean evaluation were used to assess the association between month of the year and EC detection rates. Results: This study enrolled 28,032,590 participants who underwent upper endoscopy. The number of participants in the fourth quarter (October to December: 10,923,142 [39.0%]) was 2.1 times higher than that in the first quarter (January to March: 5,085,087 [18.1%]); this trend continued for all 5 years. Contrarily, detection rates for EC in the fourth quarter (0.08/1,000 person) were half that in the first quarter (0.15/1,000 person). The odds of detecting EC were lowest in November; in 2015 the odds were 0.57 (95% confidence interval, 0.41 to 0.79; p=0.001) times lower and in 2016, they were 0.51 (95% confidence interval, 0.37 to 0.68; p<0.001) times lower compared to January. The predicted detection rates showed a decreasing trend toward the end of the year (p>0.05 for all). Conclusions: The workload of endoscopists increased excessively with the rising number of endoscopies toward the end of the year, which was reflected by the decreased EC detection rates during this period.